Bone phenotype assessed by HRpQCT and associations with fracture risk in the GLOW study - Litwic, AE; Westbury, LD; Robinson, DE; Ward, KA; Cooper, C; Dennison, EM (Springer Verlag, 2017)
The epidemiology and pathogenesis of fractures in postmenopausal women has previously been investigated in the Global Longitudinal study of Osteoporosis in Women (GLOW). To date, however, relationships between bone imaging outcomes and fracture have not been studied in this cohort. We examined relationships between high-resolution peripheral quantitative computed tomography (HRpQCT) parameters and fracture in the UK arm of GLOW, performing a cluster analysis to assess if our findings were similar to observations reported from older participants of the Hertfordshire Cohort Study (HCS), and extended the analysis to include tibial measurements. We recorded fracture events and performed HRpQCT of the distal radius and tibia and dual-energy X-ray absorptiometry (DXA) of the hip in 321 women, mean age 70.6 (SD 5.4) years, identifying four clusters at each site. We saw differing relationships at the radius and tibia. Two radial clusters (3 and 4) had a significantly lower hip areal bone mineral density (p < 0.001) compared to Cluster 1; only individuals in Cluster 4 had a significantly higher risk of fracture (p = 0.005). At the tibia, clusters 1, 3 and 4 had lower hip areal bone mineral density (p < 0.001) compared to Cluster 2; individuals in Cluster 3 had a significantly higher risk of fracture (p = 0.009). In GLOW our findings at the radius were very similar to those previously reported in the HCS, suggesting that combining variables derived from HRpQCT may give useful information regarding fracture risk in populations where this modality is available. Further data relating to tibial HRpQCT-phenotype and fractures are provided in this paper, and would benefit from validation in other studies. Differences observed may reflect age differences in the two cohorts.